The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0181110
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine protects rabbit spermatozoa against reactive oxygen species-induced damages

Abstract: The process of cryopreservation results in over-production of reactive oxygen species, which is extremely detrimental to spermatozoa. The aim of this study was to investigate whether addition of cysteine to freezing extender would facilitate the cryosurvival of rabbit spermatozoa, and if so, how cysteine protects spermatozoa from cryodamages. Freshly ejaculated semen was diluted with Tris-citrate-glucose extender supplemented with different concentrations of cysteine. The motility, intact acrosomes, membrane i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 44 publications
3
42
1
Order By: Relevance
“…There were significant differences in the number of spermatozoa bound to ZP at day 7 between the control and 50 μM NR1 groups during liquid storage at 17°C. Zhu et al have demonstrated that cysteine significantly enhances the ZP binding capacity of frozen‐thawed spermatozoa in rabbits, which are similar to our results (Zhu et al., 2017). AI fertility parameters are the most important factors for assessing spermatozoa quality.…”
Section: Discussionsupporting
confidence: 93%
“…There were significant differences in the number of spermatozoa bound to ZP at day 7 between the control and 50 μM NR1 groups during liquid storage at 17°C. Zhu et al have demonstrated that cysteine significantly enhances the ZP binding capacity of frozen‐thawed spermatozoa in rabbits, which are similar to our results (Zhu et al., 2017). AI fertility parameters are the most important factors for assessing spermatozoa quality.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies demonstrated that the addition of GSH to cryopreserved ejaculate of animals protects the sperm from the harmful effects of ROS accumulated during this process, at the same time improving sperm motility, viability, the integrity of the cell membrane, and sperm DNA, as well as the activity of antioxidant enzymes [ 50 , 51 , 52 ]. The addition of cysteine to rabbit ejaculate increased biosynthesis of intracellular glutathione and significantly affected cell membrane integrity, acrosomal inviolability or sperm motility [ 53 ]. The result of GSH meta-analysis is statistically significant ( p < 0.001), so evidence was found for differences between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…According to Zhu et al [ 29 , 40 ], the LIVE/DEAD™ Sperm Viability Kit (Invitrogen™, Shanghai, China) and fluoresce isothiocyanate-peanut agglutinin (FITC-PNA) were used for the evaluation of membrane integrity and acrosome integrity, respectively. Sperm samples were incubated with SYBR working solution (100 nM) at 37 °C for 5 min and then with PI (propidium iodide) working solution (12 μM) for another 5 min for the detection of membrane integrity.…”
Section: Methodsmentioning
confidence: 99%
“…Growing evidence has demonstrated that ROS accumulates during the cooling and freezing-thawing process [ 29 ]. Addition of proline to semen extender significantly improved donkey sperm motility after cold storage at 5 °C for three days [ 30 ].…”
Section: Introductionmentioning
confidence: 99%